Diagnostic markers of betaherpesvirus 6 infection of A and B types in children with respiratory diseases - O. V. Goleva; I. V. Babachenko; E. V. Sharipova; Е. А. Murina; Yu. A. Eismont; R. S. Kalinin; A. B. Chukhlovin; Z. А. Osipova; A. L. Mukomolova; A. V. Krylov; O. S. Glotov (Журнал инфектологии)
Objective: to reveal the prevalence of infection by various variants of betaherpesvirus 6 А/В types in children with clinical manifestations of acute respiratory disease in case of betaherpesvirus 6 type DNA identification in the blood and to specify the features of diagnostic markers during mono- and mixed herpesvirus infection.Materials and methods: there was made the analysis of clinical and laboratory data of 71 patients with the medical history of recurrent respiratory diseases or suspicion about exanthem subitum, hospitalized to Pediatric Research and Clinical Center for Infectious Diseases with the symptoms of acute respiratory disease and betaherpesvirus 6 type DNA identification in the blood. Laboratory investigation included molecular and biological methods of respiratory group and herpesviruses identification, as well as serological methods of antiviral antibodies identification.Results: among the patients hospitalized with clinical manifestations of acute respiratory infection or exanthem subitum and presence of betaherpesvirus 6 DNA in the blood, 24, 0% of the patients had the markers of respiratory viruses in swabs taken from nasopharynx, 21,1% of the cases were diagnosed as viral-bacterial infection in the patients with a complicated course of the disease. 40,8% of the cases were registered as a mixed infection caused by betaherpesvirus 6 and Epstein-Barr virus. In 99% of the cases the patients were infected by human betaherpesvirus 6В; and in 1% of the cases - by human betaherpesvirus 6 А. One patient was characterized by a constant isolation of betaherpesvirus 6 А from his blood and oropharynx scrape in invariable concentration without any dependence on the administered treatment and the disease acuity.Conclusions: betaherpesvirus 6 В was isolated in the blood of the patients in 99% of the cases, and 6 A – in 1% of the cases. The infection caused by Epstein-Barr virus was revealed more often in case of mixed infection by herpesviruses, with the markers of acute period or reactivation. The patient with confirmed betaherpesvirus 6 А had invariable virus load in his blood and oropharynx scrape that is likely to be connected with the virus genome integration in human cell DNA without provoking pathology.